1983
DOI: 10.1063/1.446148
|View full text |Cite
|
Sign up to set email alerts
|

The ν3 vibrational spectrum of the free ammonium ion (NH4+)

Abstract: The ν3 band of the ammonium ion was measured near 3.0 μm with a color center laser spectrometer using the technique of velocity modulated absorption spectroscopy. NH4+ was produced in an ac discharge containing 0.1 Torr of nH3 and 1.5 Torr of H2. Seventy individual transitions were measured with an accuracy of 1×10−6 and assigned to q0, P+, and R− branches of a tetrahedral molecule. The constants derived in a preliminary analysis are: νeff0=3342.540 2(97) cm−1, B0+B1−2B1χ3=11.110 8(35) cm−1, B1−B0=−0.050 71(45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…1 were concurrent studies by Crofton and co-workers 1,2 and by Scha¨fer and co-workers, 3,4 which yielded the assignment of the infrared-active stretching fundamental, n 3 . The other infrared-active fundamental of gas-phase NH 4 1 , n 4 , was later observed in diode laser studies.…”
Section: Introductionmentioning
confidence: 88%
“…1 were concurrent studies by Crofton and co-workers 1,2 and by Scha¨fer and co-workers, 3,4 which yielded the assignment of the infrared-active stretching fundamental, n 3 . The other infrared-active fundamental of gas-phase NH 4 1 , n 4 , was later observed in diode laser studies.…”
Section: Introductionmentioning
confidence: 88%
“…difference (171,172), Doppler tuning (173,174) difference (175) difference (176), FT emission (177,178) FT emission (177) FIR side band (179) difference (180), FIR side band (179), color (183), diode (181,182,184,185) FIR side band (179), color (186), diode (181) difference (187,188) color (189) difference (190) difference (191)(192)(193)(194), diode (194,195), Doppler tuning (196--199) color (200), diode (201,202) difference (203), color (204,205) FIR LMR (206) FIR LMR (207) FIR LMR (208) diode (209) • (M) (*) and (M) (ll) denote discharge in and pyrolysis of M, respectively.…”
Section: Transient Species Produced By Electrical Dischargementioning
confidence: 98%
“…Gudeman ct al (183) have developed a velocity-modulation technique by judiciously noting that only ion spectra are Doppler-shifted by discharge electric field; they employed an ac (1 to 8 kHz) discharge combined with lock-in detection of absorption signals. This technique has in fact proved to be useful in selectively detecting ion spectra among much more abundant spectra of neutrals and has allowed the detection ofHCO+ (183), HN; (186), NHt (203)(204)(205), H30+ (200)(201)(202), HCNH+ (187), HeH+ (172), and H2F+ (189).…”
Section: Ionic Species In a Discharge Plasmamentioning
confidence: 99%
“…[30][31][32][33][34][35][36] For example, the v 3 mode of NH 4 + was identified by Crofton and Oka 30 and by Saykally and coworkers. 31 On the other hand, the v 4 band was observed by Polak et al 35 and by Park et al 36 Spectral lines of several deuterated isotopomers have also been reported. 33,34 The spectroscopic study of molecular ions is not easy because of the difficulties associated with their generation.…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of its vibrational energy levels could offer a unique opportunity for diagnostics of the plasmas. Indeed, this molecule has been subjected to spectroscopic studies, focusing on low-lying rovibrational levels. For example, the v 3 mode of NH 4 + was identified by Crofton and Oka and by Saykally and co-workers . On the other hand, the v 4 band was observed by Polak et al and by Park et al Spectral lines of several deuterated isotopomers have also been reported. , The spectroscopic study of molecular ions is not easy because of the difficulties associated with their generation.…”
Section: Introductionmentioning
confidence: 99%